Pembrolizumab-Associated acute tubular interstitial nephritis with asymptomatic serum creatinine elevation: A case report - Kidi, Mehmet Mutlu; Bayram, Ertugrul; Kaya, Bülent; Köşeci, Tolga; Kara, İsmail Oğuz; Şahin, Berksoy (Scientific Reports in Medicine, 2026)
Immune checkpoint inhibitors (ICPIs) have transformed cancer treatment but may cause immune-related adverse events (irAEs) affecting multiple organ systems. Renal irAEs, particularly tubulointerstitial nephritis (TIN), are uncommon yet clinically significant, and their optimal diagnosis and management — including the decision to rechallenge — remain areas of active investigation.A 59-year-old male with metastatic lung adenocarcinoma and high PD-L1 expression (TPS 80%) received pembrolizumab monotherapy. After eight cycles, asymptomatic acute kidney injury (AKI; serum creatinine 2.97 mg/dL) was detected during routine monitoring. Clinical and laboratory evaluation — including peripheral eosinophilia and pyuria with leukocyte casts on urine microscopy — supported a diagnosis of TIN without recourse to kidney biopsy. The Naranjo Adverse Drug Reaction Probability Scale score was 8, indicating a probable association with pembrolizumab. Prednisolone was initiated, and serum creatinine returned to baseline within 5 days. Following complete renal recovery and a joint oncology–nephrology risk–benefit assessment, pembrolizumab was successfully rechallenged. The patient completed 12 additional cycles with stable renal function and no recurrence of AKI.This case demonstrates that pembrolizumab-associated TIN may present as entirely asymptomatic creatinine elevation, underscoring the importance of routine biochemical monitoring. A biopsy-free diagnostic approach was feasible when clinical and laboratory findings were concordant. The successful rechallenge outcome contributes to the limited evidence supporting individualized ICPI resumption following grade 3 renal irAEs.